PENERAPAN VIDEO SENAM KESEGARAN JASMANI 2012 UNTUK MENINGKATKAN GERAKAN SENAM KESEGARAN JASMANI SISWA KELAS V SD NEGERI 1 PANGGUNG BARAT MAGETAN - Mandalawati, Titin Kuntum (Premiere Educandum, 2013)
This research purposes to improve the movements of the fifth graders of the elementary school SD Negeri 1 Panggung Barat Magetan by applying the Gymnastic Video of âSenam Kesegaran Jasmani (SKJ)â 2012. This is a Classroom Action Research (CAR). The source of data are the fifth graders of SDN I Panggung Barat Magetan as many as 30. Â Data Â were Â collected Â through Â tests Â and Â observation. Â They Â are qualitatively Â described Â and Â the Â percentage Â of Â the Â distribution Â is provided. Results Â show that Â applying the Â SKJ Â video improved the movements of the fifth graders of SDN I Panggung Barat Magetan as indicated Â by Â the Â tests Â on Â their Â movements Â before Â and Â after Â the application Â of Â the Â video. Â The Â descriptive Â qualitative Â analysis improvements were visible on the cycle I, II and III in which there were Â three Â action Â meetings. Â In Â the Â first Â cycle Â it Â focused Â on Â the warming up, core and cooling-down movements. In the final meeting of the first cycle, a test was administered. In the first cycle it found improvement of Â 30% out of the 30 students i.e. 9 students. In the second cycle was reflection on the first cycle and another movementwas added. In this cycle the emphasis was on the core movements and repeating the warming up and introducing the cooling-down ones. InÂ this final meeting of this cycle, a test was administered and all students took part. The second cycle witnessed improvement of 60%, 19 out ofÂ 30 students. The third cycle was a reflection on the second cycle in addition to another movement introduction. This cycle emphasized onÂ the cooling-down movements and repetition on the warming up and core movements. In the final meeting, a test was administered to knowÂ whether or not the students improved. All of them participated. In this cycle it was found improvement of 75%, or 23 out of 30 students.Â However, there were 25 of them who could perform correctly. The percentage, Â therefore, Â changes Â into Â 80%. Â This Â is Â higher Â than Â theÂ expected one on the third cycle. It is also revealed that 19.4% or 6 students were not able to perform the gymnastic correctly.Â Key words:Â SKJ 2012 Video, Gymnastic Movements